Traditional Medicine as Mentawai Local Wisdom - Ayu Puspita Sari; Agusti Efi (Postgraduate, University of Mataram, 2024)
The Mentawai community still have a strong culture and holds a profound reverence for their heritage, particularly in the realm of traditional medicine. They continue to place significant value on traditional healing methods alongside modern medical treatments, comprising two distinct complementary healthcare systems. In this modern sophisticated era, the use of traditional medicine in Mongan Poula village has been marginalized or ignored because of the emergence of modern medicine and the entry of health teams in villages, such as doctors and nurses. Modern medicines are widely circulated in villages and even sold to stalls. This research aims to examine the media used in traditional medicine, the process of treatment, and traditional Mentawai medicine that have an impact on local wisdom. This research utilized a qualitative approach and ethnographic research type. The informant selection technique was carried out by purposive sampling. Data collection techniques used in-depth interviews, observation, and documentation studies. Data analysis employed an interactive model proposed by Miles and Huberman. The results of this study revealed that in accordance with the formulation of the problem, including: Traditional medicine media, Traditional medicine process in Mentawai society, and Mentawai traditional medicine that has an impact on local wisdom. Based on the formulation of the problem, it shows that Sikerei traditional medicine is used to treat sick people.